\[\boxed{\text{700\ (700).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[a^{3} + 27b^{3} =\]
\[= (a + 3b)\left( a^{2} - 3\text{ab} + 9b^{2} \right) =\]
\[= (a + 3b)\left( a^{2} + 6\text{ab} + 9b^{2} - 18\text{ab} \right) =\]
\[= (a + 3b)(a + 3b)^{2} - 18ab =\]
\[= 2 \cdot 2^{4} - 18ab = 8 - 18ab\]
\[8 - 18ab = 8 - 18ab.\]
\[\boxed{\text{700.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1){\ (x - 8)}^{2} - x \cdot (x + 6) = - 2\]
\[x^{2} - 16x + 64 - x^{2} - 6x = - 2\]
\[- 22x = - 66\]
\[x = 3\]
\[Ответ:x = 3.\]
\[2)\ (x + 7)^{2} = (x - 3)(x + 3)\]
\[x^{2} + 14x + 49 = x^{2} - 9\]
\[14x = - 58\]
\[x = - \frac{58}{14} = - 4\frac{1}{7}\]
\[Ответ:\ x = - 4\frac{1}{7}.\]
\[0 \cdot x = - 4\]
\[Ответ:нет\ корней.\]
\[4)\ x \cdot (x - 2) - (x + 5)^{2} = 35\]
\[x^{2} - 2x - x^{2} - 10x - 25 = 35\]
\[- 12x = 60\]
\[x = - 5\]
\[Ответ:\ x = - 5.\]